Mortality of Casuarina equisetifolia Forst. - Bakshi, B. K. (Indian Forester, 1951)
Deficiencies of water and nutrients are believed to be the causes of failure of Casuarina in the localities inspected. Trees thus weakened are, in some cases, attacked by Trichosporium vesiculosum which hastens their death. Manuring in pits prior to transplanting, deep planting and watering in the initial stages will raise a vigorous stand. Leaf litter should not be removed from the plantations. T. vesiculosum may be controlled by preventing pruning and lopping of branches, trenching and other sanitary practices.